Integration of Transformer-Based Language Models with Humanoid Robots: A Case Study Using NAO and TinyLlama for Real-Time Conversational Interaction - Souza, Vitor Amadeu (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2026)
This work presents a spoken dialogue system integrating the NAO humanoid robot with the TinyLlama-1.1B-Chat-v1.0 language model through a modular pipeline architecture that facilitates maintenance and integration with commercial robotic platforms, combining NAO’s native ASR and TTS modules with the language model; experimental results indicate a WER of 15% for a 163-word vocabulary, an average response latency of 4.2 seconds, and the ability to generate contextually appropriate responses.